2021
DOI: 10.3389/fcvm.2021.745539
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Lipid Profiles With Cardiovascular Diseases and Death in a 10-Year Prospective Cohort Study

Abstract: Background: Dyslipidemia is one of the modifiable risk factors for cardiovascular diseases (CVD). Identifying subjects with lipid abnormality facilitates preventative interventions.Objectives: To evaluate the effects of lipid indices on the risks of ischemic stroke (IS), coronary heart disease (CHD), CVD, all-cause death, and CVD death.Methods: The cohort study of 4,128 subjects started in May 2009 and followed up to July 2020. Restricted cubic spline (RCS) regression analysis was used to explore the dose-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…However, the mean HDL cholesterol of the male group (83.35 mg/dl) was much higher than that of the female group (48.35 mg/dl). The finding was in line with previous studies which indicated that the elevated levels of conventional lipids indices, including total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG), and the reduced level of high-density lipoprotein cholesterol (HDLC) contributed to the increased risk of CVD incidence ( 9 ). However, as HDL had been acknowledged so, there were actually studies stating that the levels of HDL serum hardly correlates with its quality, rendering its predictive value of cardiovascular risks inaccurate ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, the mean HDL cholesterol of the male group (83.35 mg/dl) was much higher than that of the female group (48.35 mg/dl). The finding was in line with previous studies which indicated that the elevated levels of conventional lipids indices, including total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG), and the reduced level of high-density lipoprotein cholesterol (HDLC) contributed to the increased risk of CVD incidence ( 9 ). However, as HDL had been acknowledged so, there were actually studies stating that the levels of HDL serum hardly correlates with its quality, rendering its predictive value of cardiovascular risks inaccurate ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…The clinical management of patients with cardiovascular diseases and an accurate estimation of 10-year risk are critically dependent on their level of LDL-C [ 18 ]. Maureen et al reported the new Sampson equation to estimate LDL-C more accurately than traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding 30 baseline stroke patients, the remaining 4,098 patients were followed up to July 27th, 2020 for stroke onset. For more information of this cohort, please refer to our previous published literature ( 22 ).…”
Section: Methodsmentioning
confidence: 99%